Primary ovarian leiomyoma - Reyna-Villasmil, Eduardo (2023)
Leiomyoma is a common benign mesenchymal tumor that can develop whereversmooth muscle is present; rare as a primary ovarian tumor, its origin is stillcontroversial. Primary ovarian leiomyoma is one of the rarest benign ovarian tumors,accounting for 0.5% - 1% of benign tumors and is usually seen in women between 20and 65 years of age. They are usually asymptomatic and appear incidentally duringa pelvic examination or surgery for another cause but can occasionally manifest byabdominal pain and palpable mass. Definitive diagnosis is difficult before surgicalremoval. Because there are no pathognomonic symptoms and no characteristicimaging, the main differential diagnoses include fibroma, thecoma, sclerosingstromal tumor and leiomyosarcoma. Immunohistochemical staining is essential foraccurate diagnosis and should be considered in the differential diagnosis of ovarianspindle cell tumors. A case of primary ovarian leiomyoma is presented.